Elastic and hierarchical carbon nanofiber aerogels and their hybrids with carbon nanotubes and cobalt oxide nanoparticles for high-performance asymmetric supercapacitors. (March 2020) - Zhang, Ming; Yang, Dongzhi; Zhang, Shiyi; Xu, Ting; Shi, Yongzheng; Liu, Yaxin; Chang, Wei; Yu, Zhong-Zhen
Abstract: Although lightweight and elastic carbon nanofiber (CNF)-based aerogels are promising in wearable supercapacitors, it is still a serious issue to produce CNF-based aerogels with satisfactory integrated properties of mechanical strength, compression resilience, conductivity, and electrochemical performances. Herein, elastic aerogel anode materials with welded CNFs are fabricated by electrospining polyacrylonitrile nanofibers with polyvinylpyrrolidone as a solder to weld adjacent nanofibers followed by freeze-drying, carbonization, and CO2 activation, exhibiting remarkable electrical conductivity, excellent reversible compressibility, and a high specific capacitance of 300 F g −1 at 0.3 A g −1 . Furthermore, carbon nanotubes (CNTs) are uniformly grown on the CNF surface of the aerogels with the catalysis of metallic Co, while the Co nanoparticles at the CNT tips are oxidized in situ to Co3 O4 nanoparticles. The CNF-CNT-Co3 O4 hybrid aerogel as a hierarchical cathode exhibits a high specific capacitance of 2376 F g −1 at 1 A g −1 . An assembled asymmetric supercapacitor with the activated CNF aerogel as its anode and the hybrid aerogel as its cathode exhibits a considerably high energy density of 48.1 W h kg −1 at 780.2 W kg −1 . This study provides a new strategy for constructing lightweight and elastic electrode materials for highly efficient energy-storage application. Graphical abstract: Elastic and hierarchical carbon nanofiber aerogel and its hybrid with carbon nanotubes and cobalt oxide nanoparticles are synthesized for high-performance asymmetric supercapacitor with a high energy density of 48.1 W h kg −1 at 780.2 W kg −1 . Image 1